Alinhamentos globais de duas sequências genéticas: resultados ótimos em espaço linear - Costacurta, Matheus (2019)
Bioinformatics is an application of computational, statistical and mathematical techniques for the analysis, interpretation and control of biological data, mainly related to genetics. A frequent tasks in this area is the sequence alignment, which uses a cost function to present an optimum alignment between related sequences. This task is frequent since it is used to compare genetic material and to construct the taxonomy of living beings. The space complexity of the known exact algorithms to present more than one optimum alignment between two genetic sequences is (), where and are the sizes of the two sequences given by the number of base pairs. This space complexity may be unwanted, since the size of the sequences can reach millions of bases. Hence, many authors use heuristics, more efficient in the use of space, but without the certainty of optimality. This work, however, aims to develop a linear space complexity exact algorithm to find more than one optimum alignment between two genetic sequences.